Doktrin Gereja (Eklesiologi) - Sarmauli; Ameliatera; Jeni Utary; Sopiani; Sella Vinisya (CV Edujavare Publishing, 2024)
The church is a spiritual container where saved people enter into the fellowship of the Body of Christ. The word